2015
DOI: 10.3389/fnagi.2015.00114
|View full text |Cite
|
Sign up to set email alerts
|

Can insulin signaling pathways be targeted to transport Aβ out of the brain?

Abstract: Although the causal role of Amyloid-β (Aβ) in Alzheimer’s disease (AD) is unclear, it is still reasonable to expect that lowering concentrations of Aβ in the brain may decrease the risk of developing the neurocognitive symptoms of the disease. Brain capillary endothelial cells forming the blood-brain barrier (BBB) express transporters regulating the efflux of Aβ out of the cerebral tissue. Age-related BBB dysfunctions, that have been identified in AD patients, might impair Aβ clearance from the brain. Thus, ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 185 publications
0
26
0
Order By: Relevance
“…Corresponding to this compensatory mechanism, the present study expectedly demonstrated an increased fasting serum insulin level following IR, which directly implicated that physiological hyperinsulinemia ocurred in response to NO2 inhalation. Insulin in the serum is transported by the CSF and can cross the BBB into the brain (Vandal et al, 2015). There is evidence that chronic peripheral hyperinsulinemia (as occurs in IR) leads to a reduction of insulin transport across the BBB and affects all of the actions of insulin in the brain (Neumann et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding to this compensatory mechanism, the present study expectedly demonstrated an increased fasting serum insulin level following IR, which directly implicated that physiological hyperinsulinemia ocurred in response to NO2 inhalation. Insulin in the serum is transported by the CSF and can cross the BBB into the brain (Vandal et al, 2015). There is evidence that chronic peripheral hyperinsulinemia (as occurs in IR) leads to a reduction of insulin transport across the BBB and affects all of the actions of insulin in the brain (Neumann et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic changes in the brain tissue of AD patients are: (a) hyperphosphorylated tau protein rich intra-neuronal neurofibrillary tangles (NFT); (b) extracellular senile plaques of aggregated amyloid β (Aβ) peptides; and (c) brain tissue atrophy, starting in the entorhinal region and the temporal lobe, and progressing to the limbic system and the neocortex [ 4 , 5 , 6 , 7 , 8 , 9 ]. Most patients with AD have a sporadic, late onset form, where the major risk factors are aging, type 2 diabetes (T2D) and apolipoprotein E ε4 (APOE-ε4) [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Etiology Of Admentioning
confidence: 99%
“…Similarly, the regulated transport of soluble Aβ monomers across the blood-brain barrier by low-density lipoprotein receptor-related protein 1, ATP binding cassette transporters, and advanced glycation end product-specific receptor is critical to maintaining non-cytotoxic levels of Aβ in the brain (Shibata et al, 2000; Deane et al, 2003). Importantly, diverse intercellular and metabolic signals such as insulin might have a direct role in the regulation of Aβ transport into and out of neural tissues (Vandal et al, 2015). …”
Section: Neurodegenerative Disorders: Ipsc Models Induced Neuralmentioning
confidence: 99%